PROJECT MANAGEMENT MATURITY: AN ANALYSIS WITH FUZZY EXPERT SYSTEMS - Souza, Helder Jose Celani de; Salomon, Valerio Antonio Pamplona; Da Silva, Carlos Eduardo Sanches; Aguiar, Dimas Campos (Brazilian Journal of Operations & Production Management, 2013)
The assessment of Project Management is a growing business practice. It can be verified with the development of several Project Management Maturity (PMM) models. This paper reports results of a survey on the PMM of Brazilian companies. That survey was based on a well known PMM model. A Fuzzy Expert System was applied to deal with model’s subjectivity and to check the consistency of survey’s responses. Methodological approaches of previous PMM researches only included general statistical analysis. This way, the present work innovates when presents the usage of intelligent techniques, as Fuzzy Sets and Expert Systems, in the PMM analysis.